Peak of Covid-19 Case Increase: Factors Related to Acceptance of the Covid-19 Booster Among Adolescents - Putri, Santy Irene; Arie Jefry Ka’arayeno; Siti Asiyah; Joel Rey Ugsang Acob (Universitas STRADA Indonesia, 2025)
Background: The acceleration of booster vaccination targets a minimum of 50 percent people aged 18 years and above while still prioritizing high-risk groups, such as the elderly. This is crucial to extend the protection of the Covid-19 vaccine and ensure that there is no surge in cases in the future. Purpose: This study aimed to analyze the determinant factors of Covid-19 booster acceptance among adolescents aged 18-24 years. Methods: The present study adopted an analytic observation method with a cross-sectional approach. It took place in East Java and involved 1415 adolescents selected through a simple random sampling. The dependent variable was Covid-19 booster acceptance among these adolescents. The independent variables were age, education, gender, and family income. The data were obtained through a questionnaire. They processed using bivariate analysis to investigate the relationship between the dependent and independent variables. To determine the acceptance of adolescents towards Covid-19 booster, it used multivariate logistic regression. Results: Age (OR= 1.71, CI 95% = 1.25 to 2.3, p= 0.001), education (OR= 1.56, CI 95% = 1.18 to 2.08, p= 0.002), gender (OR= 1.51, CI 95% = 0.14 to 1.99, p= 0.004), and family income (OR= 1.36, CI 95% = 0.10 to 1.85, p= 0.052) hold a statistically significant relationship with Covid-19 booster acceptance among adolescents. Conclusion: Age, education, gender, and family income are factors affecting Covid-19 booster acceptance among adolescents. Government and other relevant stakeholders are expected to take comprehensive measures to increase Covid-19 booster vaccination among adolescents aged 18-24 years.